Ergebnisse der Wüstungsforschung in Tlaxcala (Mexiko) - Trautmann, Wolfgang (ERDKUNDE, 1974)
The development of the cultural landscape in Tlaxcala since the Conquest has been moulded by the desertion process in colonial times, whose effects reach into the most recent times. Because of the special situation of the study area, research has been concentrated on complete settlement desertions. It could be established that, between the 16th century and today, almost 40% of all settlements were deserted. Of these, over 70% could be precisely located with the help of locational references in documents, topographic names and archaeological remains. In the spatial distribution of the desertions, prominence is given on the one hand to the concentration on the periphery of Tlaxcala and, on the other, the locations away from the waterway network. Almost all the settlements which disappeared fall into the period between 1539 and 1764, with the period 1557-1627 containing about 80% and thus showing the highest intensity of desertation. The main causes were population decline through epidemics, state amalgamation of settlements and expansion of haciendas.